Professor Aleksandr Matveevich Karyakin (on the 100th anniversary of the birth) - M. V. Melnikov; M. A. Ivanov; P. A. Susla; P. V. Panfilov (Вестник хирургии имени И.И. Грекова)
August 4, 2022 marks the 100th anniversary of the birth of professor, doctor of medical sciences Aleksandr Matveevich Karyakin. Aleksandr Matveevich graduated from the Naval Medical Academy (NMA) in 1945. In 1978, A.M. Karyakin was elected to the post of head of the Department of General Surgery of Leningrad Sanitary and Hygienic Medical Institute - now North-Western State Medical University named after I.I. Mechnikov. During the years of the clinic's leadership, his natural qualities, organizational abilities and breadth of academic interests were especially clearly manifested. Unprecedented dedication, extremely responsible attitude to the work were the main features of Professor A.M. Karyakin.